Cast Metal Definitive Obturator Prosthesis for Hemi-maxillectomy Patient: A Case Report - Mirna Garhnayak1, Vijay Kumar2, Lokanath Garhnayak3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Maxillary jaw defect produced due to traumatic, surgical or congenital reason often creates communicationbetween antrum and nasopharynx. The defect not only causes nasal reflux during swallowing but also interferewith articulation and production of speech. These limitations are commonly overcome by restoration of thedefect with a prosthesis called an obturator. This case report focuses on the prosthetic rehabilitation of apost-surgical maxillary defect with cast metal definitive obturator.